The effects of hearing deficits on student self-perceptions of social belonging, difficulty at school, and self-image - Lindsy Cox; Brittany Ruffo; Julian Laird; Benjamin P Schade; Karen H Larwin (International Journal of Evaluation and Research in Education (IJERE), 2019)
A paucity of research exists that examines how well hearing-impaired students function in the primary and secondary grades when attending a general education setting. The research that does exists to suggest that issues of poor self-perception, challenges regarding a sense of belonging, and self-image may be amplified for the non-hearing student. The current investigation examines the self-reported feelings of the hearing-impaired students relative to the student with no identified hearing difficulties. Results suggest that while social belonging may be a problem for the hearing-impaired students relative to their hearing peers, no differences were found on the responses associate with self-image or trouble at school.